The impact of revenue structure on the financial performance of general colleges and universities in China - Yuyan, Hou; Halim, Hazianti Abdul; Basri, Mohd Faizal (International Journal of Evaluation and Research in Education (IJERE), 2025)
Despite the continuous increase in total funding for general colleges and universities in China, these institutions face challenges related to insufficient educational funds and inefficient fund utilization, leading to suboptimal financial performance. Therefore, the main purpose of this study is analyzing their revenue structures, which comprise the proportion of financial subsidy revenue, career revenue and other revenue and to examine the impact of revenue structures on their financial performance (measured by talent cultivation, scientific research, and social services). This study builds linear regression models and combines panel data of general colleges and universities from 2010 to 2021 to study the impact of revenue structure on their financial performance. The findings indicate that the revenue of general colleges and universities in China is based mainly on financial subsidy revenue, with the proportion of such revenue increasing annually. The financial performance of these institutions also predicates an increasing trend. Most importantly, regression analysis shows that financial subsidy revenue has a positive impact on financial performance, whereas career revenue and other revenue negatively impact financial performance. Thus, Chinese general colleges and universities should prioritize increasing financial subsidy revenue while carefully managing career and other revenue to enhance financial performance.